Solid Multicystic Ameloblastoma Misdiagnosed Radiographically as a Periapical Cyst: A Case Report - Kamath, Jasmine Shanthi; Kini, Raghavendra; Naik, Vathsala (Journal of Dentistry Indonesia, 2018)
Ameloblastoma is a rare odontogenic neoplasm occurring in the jaw that can be observed as several different histologic and radiographic presentations. Since inadequate treatment is associated with high recurrence rate, accurate diagnosis is critical for proper management of ameloblastoma. The preferred treatment is wide local excision and reconstruction. We herein present a patient with solid multicystic ameloblastoma involving the mandible, which was initially misdiagnosed and treated as a periapical cyst, and discuss various radiographic presentations of ameloblastoma.